Kids daily flip planner / Gladys Sebi Entigar ... [et al.] - Entigar, Gladys Sebi; Mohd Jamil, Milfadzhilah; Ahmed, Roziana; Talib, Nashrah (Universiti Teknologi MARA, Kedah, 2023)
The idea of Kids daily flip planner is created from a used calendar and turned into a useful planner that will be beneficial for children within the age of 6 years and above. Instead of throwing away the calendar, it is better that the calendar be recycled and be used for other new products like a planner. This used calendar is innovated into a planner that can help parents in planning their children’s activities daily during weekdays, weekends and school holidays. The planner uses simple English language with translation of Bahasa Melayu and it includes pictures or images that are easy for children to understand. Kids daily flip planner includes activities throughout the day that can be a guide for children. Among them are daily activities from morning to noon, from noon to evening andevening to at night. Therefore, this planner is divided into several sections according to daily activities at a predetermined time. For example, the planner for the activities from evening to night during weekdays will start with sport activity, taking bath, prayer, dinner, doing school work, packing the school bag, brushing teeth and going to bed. By looking at this planner, children will do their activities as directed in the planner without supervision by their parents. There are five different daily activities that parents can choose from this planner. Just like a calendar, this planner can be folded and flipped, it can stand on its own and is easy to carry anywhere. Physically, this planner hasergonomic features as it was made of hard paper and has a binding ring where it is durable and not easily damaged. Apart from that, this used calendar has been improved by putting a plastic on each page of the calendar to make it easier for children to write down or tick the activities they have completed. Therefore, this planner will come with an erasable marker pen that can be written on a plastic surface. Other features will be the colorful words and interesting images that may be easier to be understood and to be remembered by the children. Indirectly, the Kids daily flip planner acts as a guide for children to become independent and self-confident. Besides that, children will become moredisciplined and organized in managing daily activities without parental guidance. For busy parents, the Kids daily flip planner will be a useful resource in educating their children to manage time with beneficial activities. In addition, with the Kids daily flip planner, parents do not have to worry about directing their children's activities all the time because their children can follow the instructed plannerby themselves.